Case Studies on Thiamine Replacement Therapy: For Suspected Cardiac Beriberi in Children and Literature Review (The Journal of Ad-din Women's Medical College, 2025)
Thiamine (vitamin B1) serves as an important cofactor in metabolism and energy production. It is related to the biosynthesis of neurotransmitters and the production of substances used in defense against oxidative stress. Lack of thiamine affects several systems of the body, predominantly the cardiovascular and nervous systems. The cardiac effect caused by thiamine deficiency is known as cardiac beriberi, also known as wet beriberi. Other than wet beriberi, dry beriberi presents with neurological symptoms. The more severe form is Shoshin beriberi with cardiac failure and lactic acidosis with cold periphery as the presenting feature. The disease is now very rare in developed countries in this era, but still present in South East Asia and developing countries including Bangladesh. Thiamine deficiency (TD) is an important public health problem because almost all of the populations in this area consume polished rice, which is the major staple food, and other primary dietary sources of thiamine are also poor. TD is frequently missed by pediatricians, with potentially fatal consequences. Herein, we present a series of cases to draw attention to cardiac beriberi. We believe that these cases will help prompt us to the importance and also a reminder of this forgotten but notable disease.The Journal of Ad-din Women's Medical College; Vol. 13 (1), Jan 2025; p 18-22